Perlindungan P2TP2A Terhadap Hak Anak Sebagai Korban Penganiayaan Ditinjau Dari Prespektif Hak Asasi Manusia - Helmi Kaani; Dian Ekawaty Ismail; Suwitno Yutye Imran (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
This research aims to describe and analyze P2TP2A Protection for the Rights of Children Victims of Abuse Seen from a Human Rights Perspective and to analyze the factors inhibiting P2TP2A Protection for the Rights of Children Victims of Abuse Seen from a Human Rights Perspective. The method of this research is empirical. The results of the research show that P2TP2A Protection of the Rights of Children Victims of Abuse Seen from a Human Rights Perspective in Gorontalo Regency is carried out through 4 (four) aspects, namely: (1) the role of the juridical aspect, (2) the role of the legal aspect. psychological, (3) the role of the medical aspect, (4) the role of the mentoring aspect in curative and rehabilitative programs. The inhibiting factors consist of 2 (two), namely: (1) internal factors, including financial resources, human resources, unavailability of counselors and legal assistance, (2) external obstacles, including: people who do not understand the importance of protecting children's rights , attitudes of victims and victims' families, perceptions of victims' families.